Lateral Moho variations and the geometry of the Main Himalayan Thrust beneath the Nepal Himalayan orogen revealed by teleseismic receiver functions. Issue 2 (17th May 2018) - He, Ping; Lei, Jianshe; Yuan, Xiaohui; Xu, Xiwei; Xu, Qiang; Liu, Zhikun; Mi, Qi; Zhou, Lianqing
SUMMARY: The lateral Moho variations and the geometry of the Main Himalayan Thrust under the Nepal Himalayan orogen are investigated to determine a new crustal model using a large number of high-quality receiver functions recorded by the HIMNT and HiCLIMB portable seismic networks. Our new model shows an evident and complicated lateral Moho depth variation of 8–16 km in the east–west direction, which is related to the surface tectonic features. These results suggest a non-uniformed crustal deformation, resulted from the splitting and/or tearing of the Indian plate during the northward subduction. Our migrated receiver function images illustrate a discernible ramp structure of the Main Himalayan Thrust with an abrupt downward bending close to the hypocentre of the 2015 Gorkha M w 7.8 earthquake. The distribution of the aftershocks coincides with the present decollement structure. Integrated with previous magnetotelluric soundings and tomographic results, our results suggest that the ramp-shaped structure within the Main Himalayan Thrust could enhance stress concentration leading to the nucleation of the large earthquake. Our new crustal model provides new clues to the formation of the Himalayan orogen.